2017
DOI: 10.3126/kumj.v13i4.16833
|View full text |Cite
|
Sign up to set email alerts
|

Study of Clinical Variables Affecting Long Term Outcome after Microdisectomy for Lumbar Disc Herniation

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 16 publications
4
14
1
Order By: Relevance
“…The current study showed better clinical and functional outcomes with early surgical intervention by microdiscectomy as reported by studies [8][9][10][11][13][14]16,18] while study of Shrestha et al [12] showed no signi cant correlation between duration of symptoms and ODI. Gelalis et al [17] showed no impact of duration of symptoms on clinical outcomes.…”
Section: Comparison With Other Studiessupporting
confidence: 73%
See 1 more Smart Citation
“…The current study showed better clinical and functional outcomes with early surgical intervention by microdiscectomy as reported by studies [8][9][10][11][13][14]16,18] while study of Shrestha et al [12] showed no signi cant correlation between duration of symptoms and ODI. Gelalis et al [17] showed no impact of duration of symptoms on clinical outcomes.…”
Section: Comparison With Other Studiessupporting
confidence: 73%
“…There are many factors can affect the clinical and functional outcomes after lumbar microdiscectomy as duration of symptoms before surgery. Although, there is no agreement among the previous studies about the certainty of the effect of preoperative duration of symptoms on patients' clinical and functional outcomes after microdiscectomy and absence of randomized controlled trial regarding this issue [8][9][10][11][12][13][14][15][16][17][18].…”
Section: Introductionmentioning
confidence: 98%
“…concluded that more or less than 12 months duration of preoperative sciatica may not affect the surgical outcomes of simple disc herniation after discectomy. Shrestha et al 12 . showed in their study that preoperative duration of symptoms did not affect the post‐operative patients' outcomes measured by Oswestry Disability Index (ODI).…”
Section: Introductionmentioning
confidence: 97%
“…3 Nepal Journal of Neuroscience, Volume 18, Number 1, 2021 There have been very few studies looking into the postoperative quality of life of these patients in Nepalese population. 4 There are various QOL related questionnaires available. Among them the Short Form-36(SF-36) is a standardized questionnaire for measuring QOL.…”
Section: Introductionmentioning
confidence: 99%